2005
DOI: 10.1021/jp0536549
|View full text |Cite
|
Sign up to set email alerts
|

CO Adsorption on CoMo and NiMo Sulfide Catalysts:  A Combined IR and DFT Study

Abstract: Experimental IR spectra of carbon monoxide adsorbed on a series of Mo/Al2O3, CoMo/Al2O3, and NiMo/Al2O3 sulfided catalysts have been compared to ab initio DFT calculations of CO adsorption on CoMo and NiMo model surfaces. This approach allows the main IR features of CO adsorbed on the sulfide phase to be assigned with an uncertainty of 15 cm(-1). On the CoMo system, the band at 2070 cm(-1) is specific of the promotion by Co and is assigned to CO interacting either with a Co atom or with a Mo atom adjacent to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 35 publications
9
82
0
Order By: Relevance
“…7) that exhibits stable CUS sites under typical hydrotreating conditions [39]. The h 1 adsorption energies are similar to the ones observed for the unpromoted catalyst.…”
Section: Adsorption On Non-promoted and Promoted Surfacessupporting
confidence: 71%
See 1 more Smart Citation
“…7) that exhibits stable CUS sites under typical hydrotreating conditions [39]. The h 1 adsorption energies are similar to the ones observed for the unpromoted catalyst.…”
Section: Adsorption On Non-promoted and Promoted Surfacessupporting
confidence: 71%
“…Figure 5 shows the IR spectrum of CO adsorbed on the freshly sulfided CoMo/Al 2 O 3 catalyst (spectrum a). It leads to the appearance of bands at 2 186 and 2 154 cm -1 corresponding to CO interacting with Lewis acid sites (Al 3+ ) and acidic AlO-H groups of the uncovered alumina support, a band at 2 110 cm -1 characterizing non promoted CUS Mo edge sites [39] and two bands at 2 070 and 2 052 cm -1 corresponding to promoted CUS sites in various environments [40].…”
Section: Infrared Characterization Of Phenol and 2-ethylphenol Adsorpmentioning
confidence: 99%
“…There is thus a striking agreement between the DFT calculations and STM experiments, which both reveal that Co prefers to be located at the S-edge, whereas Ni is present on both S-and M-edge. Combined IR and DFT studies of CO adsorption on Co(Ni)Mo sulfide catalysts have also suggested that low wavenumbers (below 2060 cm -1 ) are the signature of Mo centers adjacent to promoter atoms, confirming partial edge decoration [74].…”
Section: Nano-crystallite Morphologiesmentioning
confidence: 97%
“…It is believed that the Co atoms are mostly localized on the S-edges, although in the case of a high Co/Mo ratio, some Co atoms are also located on the Mo-edges. 12 Co atoms can substitute for Mo atoms at these edges, which results in S-vacancies since the Co ions have a lower valency than the Mo ions. 13 This generates new active sites.…”
Section: Introductionmentioning
confidence: 99%